NUTRITIVE VALUE OF FIELD PEA – OAT AND COMMON VETCH – OAT BICROPS - Markovic, Jordan P; Milenković, Jasmina; Petrović, Mirjana; Zornić, Vladimir; Racić, Nedeljko; Stepić, Marija; Blagojević, Milomir (Journal of Agricultural Sciences (Belgrade), 2023)
Peas and vetches are the most important plant species for the production of forages, where they can be used as hay, haylage or silage. Due to its specific characteristics – tendecy to lodging and high buffering capacity, it is most grown in a mixture with small grains, as support crops, in order to prevent or reduce lodging, reduce bufering capacity, and at the same time obtain biomass suitable for the ensiling process. In pure crops, peas are most often used as green feeds or hay in the stage of formation the first pods, while the best quality of vetches dry matter have been achieved by using it in the stage of full flowering or the beginning of the formation the first pods, when up to 25% of crude protein is obtained in the biomass of pure culture. The level of protein and other nutrients, especially carbohydrates, depends on the stage of development of the plant species in the mixtures. Advancement in the satge of growth and plant development leads to a decrease in the leaf to stem ratios in the biomas with a simulataneous increase in the fibres ratios (cellulose, hemicellulose, and especially lignin), which affects the decrease in digestibility and utilization of nutrients. Because of all of these mentioned above, it is particularly important to choose the right harvesting moment in order to balance the yield and nutritional value of feeds used in bicrops.